Neuropedagogy for Improving the Educational Process in Universities - Nurmakhanova, Dina E.; Rakhmetova, Aiman K.; Kassymbekova, Dinara A.; Meiirova, Gulzhamila; Rakhimzhanova, Gaukhar M. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Objective: This study aims to investigate the problems that neuropedagogy can solve in the context of the educational process. Background: Research in neuropedagogy has been gaining popularity in recent years. This has been driven by advances in technology and the social sciences. Every year more and more scientists approach the subject of neuropedagogy to modernise the educational system and improve the educational process. Method: The main research methods in this scientific article are the comparative method, methods of analysis and data synthesis, the historical method, as well as the theoretical analysis of scientific literature related to the subject matter. Results: The study explored the concept of neuropedagogy and the principles on which it is based. Practical recommendations for teachers of Kazakhstan have been developed. Scientific articles on the subject matter are analysed, the degree of research and the effectiveness of the implementation of neuropedagogy in the educational process is assessed. Conclusion: It was concluded that the use of neuropedagogy would provide an opportunity to improve and modernise the education system.